Establishment of Creative Convergence Curriculum for Systematic Management of MZ Generation - LEE, Choong Hyong (International Journal of Membrane Science and Technology, 2023)
A new generation of creativity (New-Collar) has arrived, not White-Collar or Blue-Collar. The main characteristics of the creative generation are the Fourth Industrial Revolution, the generation that makes good use of digital content and digital devices, expresses their tastes and colors well, and produces and consumes new things. Interest in Metaverse education that is scalable and realistic beyond space-time boundaries is growing, with the advent of the new normal era, in which non-face-to-face training has become every day’s work. With the technology development, the emergence of new educational services, and the changes in the environment at that time, the Metaverse education develops in various forms and is used in a variety of meanings. For this motivation, this study intends to examine earlier studies including curriculum procedures and present a model for creating a future creative convergence theme through a questionnaire. In addition, we intend to create a blueprint for convergence of university creativity and develop a plan to promote the design of creative convergence themes for the digital generation. This study is intended to help educational institutions think about designing curricula for the digital generation.